Crypto in Ulama Studies: Legal and Ethical Perspectives on the Use of Cryptocurrency - Mustofa Anwar; Ema Puspitasari; Samuel Karim (Journal of Islamic Economy and Business (JIsEB), 2024)
Cryptocurrency has become a hot topic in the global economy and finance. However, from the perspective of Islamic law and ethics, it is still not comprehensively understood. In this situation, the purpose of this research is to find out more deeply the scholars' views on the use of Cryptocurrency which is focused on legal and ethical aspects in Islamic economics. This study uses a normative-comparative approach as a reference to analyze the fatwa of ulama on cryptocurrencies. The ulama's fatwa used is the fatwa of the Indonesia Ulema Council (MUI), the Dar al-Ifta' fatwa and the results of Bahtsul Masail Nahdlatul Ulama (NU). The results of the study concluded that the opinions of scholars about cryptocurrency differed, there are some scholars who view cryptocurrency as something that is in accordance with Sharia and halal principles, and most scholars view cryptocurrency as something that has the potential to contain uncertainty and that gambling is prohibited in Islam. The implication of this research is to encourage the creation of strict regulations on cryptocurrencies that can ensure security in transactions according to Sharia principles.